The Relation between eNOS -786 C/T, 4 a/b, MMP-13 rs640198 G/T, Eotaxin 426 C/T, -384 A/G, and 67 G/A Polymorphisms and Long-Term Outcome in Patients with Coronary Artery Disease - Kincl, Vladimír; Máchal, Jan; Drozdová, Adéla; Panovský, Roman; Vašků, Anna (Disease markers, 2015)
AIM: The purpose of this study is to determine the association between eotaxin 426 C/T, -384 A/G, 67 G/A, eNOS -786 T/C, 4 a/b, and MMP-13 rs640198 G/T and prognosis of patients with known CAD. METHODS: From total of 1161 patients referred to coronary angiography, 532 patients with angiographically confirmed CAD were selected. Their long-term outcome was followed up using hospital database. Subsequent events were assessed in this study: death or combined endpoint-myocardial infarction, unstable angina pectoris, revascularization, heart failure hospitalization, and cardioverter-defibrillator implantation. RESULTS: The multivariate Cox regression model identified age, smoking, and 3-vessel disease as significant predictors of all-cause death. Further analysis showed that eotaxin 67 G/A (GA + AA versus GG) and eotaxin -384 A/G (GG versus GA + AA) were significant independent prognostic factors when added into the model: HR (95% CI) 2.81 (1.35-5.85), p = 0.006; HR (95% CI) 2.63 (1.19-5.83), p = 0.017; eotaxin -384 A/G was significantly associated with the event-free survival, but it did not provide the prognostic information above the effect of two- or three-vessel disease. CONCLUSION: The A allele in eotaxin 67 G/A polymorphism is associated with worse survival in CAD patients.
Keywords: senioři; jednonukleotidový polymorfismus; nemoci koronárních tepen; Middle Aged; mužské pohlaví; Matrix Metalloproteinase 13; studie případů a kontrol; Chemokine CCL11; Nitric Oxide Synthase Type III; matrixová metaloproteinasa 13; Coronary Artery Disease; ženské pohlaví; Humans; synthasa oxidu dusnatého, typ III; lidé středního věku; Case-Control Studies; Female; Aged; chemokin CCL11; lidé; Male; Polymorphism, Single Nucleotide